Isolation and characterization of Klebsiella pneumoniae specific bacteriophages from sewage samples - Kumari, S; Harjai, K; Chhibber, S (Folia microbiologica, 2010)
Five bacteriophages (Kpn5, Kpn12, Kpn13, Kpn17 and Kpn22), each having specificity against Klebsiella pneumoniae strain B5055, were isolated from sewage samples and characterized in terms of growth characteristics, genetic material, morphology and structural proteins. Adsorption rate as well as single step growth curve experiments showed variation among phages. Restriction enzyme digestion of DNA confirmed the presence of double stranded DNA as well as the heterogeneous nature of genetic material. RAPD-PCR was performed to further distinguish these closely related phages. Their genome fingerprint confirmed their diversity. Transmission electron microscopy, on the other hand, showed their morphological similarity; they were assigned to family Podoviridae, order Caudovirales on the basis of their head and tail morphology. Structural proteins resolved on SDS-PAGE showed the presence of similar major outer membrane proteins. The bacteriophages, belonging to Podoviridae family with short stumpy tails, were found to be nontoxic to mice. They showed maximum count in various organs at 6 h post inoculation, which persisted till 36 h. These phages thus have the potential to be used for phage therapy.
Keywords: elektroforéza v polyakrylamidovém gelu; DNA fingerprinting; Mice, Inbred BALB C; genotyp; odpadní vody; přichycení viru; DNA; DNA Fingerprinting; Genotype; virion; Klebsiella pneumoniae; Sewage; DNA virů; genetická variace; transmisní elektronová mikroskopie; technika náhodné amplifikace polymorfní DNA; Mice; Genetic Variation; Electrophoresis, Polyacrylamide Gel; Viral Proteins; zvířata; Random Amplified Polymorphic DNA Technique; Bacteriophages; Podoviridae; anatomické struktury zvířat; Microscopy, Electron, Transmission; myši inbrední BALB C; DNA, Viral; myši; Virus Attachment; bakteriofágy; Virion; virové proteiny; Animal Structures; Animals